Wage Drift and the Relevance of Centralised Wage Setting - S. Holden (University of Oslo, Department of Economics, 1998)
The system of wage setting in the Nordic countries is often regarded as highly centralised, contributing to considerable real wage flexibility. This view has been questioned, as the sizeable wage drift may offset the effect of the central negociations. This paper presents evidence from the four major Nordic countries, suggesting that there is no or little such offsetting effect. Yet the institutional system of wage formation may induce nominal rigidities at the central negociations, that may prevent wage restraint when there is little room for money wage growth.
Keywords: J5; 330; wages